Remnants of populations provide effective source material for reintroduction of an endangered Hawaiian plant, Schiedea kaalae (Caryophyllaceae)1. Issue 11 (1st November 2014) - Weisenberger, Lauren A.; Weller, Stephen G.; Sakai, Ann K.
Abstract : Premise of the study: Reintroductions may be essential to prevent extinction of many critically endangered species. Ideally, reintroduction efforts rely on adjacent source populations, but limited source material may necessitate crossing individuals from different and possibly distant populations. To determine the consequences of integrating multiple populations in reintroductions, we investigated levels of inbreeding depression, outbreeding depression, and heterosis for populations of Schiedea kaalae (Caryophyllaceae), an endangered species endemic to the Wai'anae and Ko'olau Mountains of O'ahu, Hawai'i. The possibility of gene flow among plants was explored through pollinator observations. Methods: Individuals from ex situ living collections of nine populations were hand‐pollinated with pollen from the same plant, plants from the same population (for three populations only), or plants from different populations. Progeny were outplanted into two common gardens, one in each mountain range on O'ahu. Cumulative fitness was estimated using several independent life history stages. Key results: Inbreeding depression was minimal, and no outbreeding depression was detected. In contrast, strong heterosis was evident in progeny from between‐population crosses, which had higher relative fitness than progeny from self‐pollinations or within‐population crosses. Observations of floral visitors provided the first evidence that biotic pollination may be important for this species. Conclusions: Results demonstrate the ability to conduct genetic rescue of rare species and suggest that reintroductions may be most successful using heterotic individuals from crosses between populations and at sites where pollinators are present and promote outcrossing.